Descriptive Analysis of Taste Characteristics of Baijiu and Construction of Its Taste Wheel - HE Yingxia, XIE Kaijun, WANG Gaowei, CHEN Shuang, XU Yan (Shipin Kexue, 2025)
To address the limitation in sensory evaluation of taste characteristics of baijiu, this study systematically gathered taste descriptors of baijiu from literature reviews, baijiu review websites, consumer questionnaire survey, and descriptive analysis of baijiu samples collected from multiple sources. The taste descriptors were screened, sorted out and classified by domestic and international methods for flavor wheel construction of liquors. A total of 38 taste descriptors were identified, which were primarily classified into five categories, namely, basic taste, pungency, texture, body and aftertaste, and defined or interpreted. Besides, the citation frequency of each descriptor was determined by selecting appropriate items. Finally, a taste wheel of baijiu with a relatively quantitative reference framework was constructed. Its development and application provide a powerful and effective auxiliary tool for the quality evaluation and promotion of baijiu.